The Effect Of Students Centered Learning (SCL) Strategy On Students’ Achievement In Studying Psycholinguistics - Yani Lubis; Idris Siregar; Idris Sadri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
There are several ways to teach Psycholinguistics. Even though, there are many ways or theories in teaching and learning to increase students’ achievement in learning Psycholinguistics but not all of those theories and ways are successes. This research will find out the effective way to teach Psycholinguistics for Department of English Educational students of Faculty of Tarbiyah Science and Teacher Training of State Islamic University North Sumatra (UIN-SU) Medan. Each member of a team is responsible not only for learning what is taught but also for helping teammates learn, thus creating an atmosphere of achievement. The aims of this research: to know the students’ difficulties in learning Psycholinguistics, to know how is the lecturer implement Students Centered Learning (SCL) Strategy in teaching learning process special for teaching Psycholinguistics, and to know if there significance effect of Students Centered Learning (SCL) Strategy on students’ achievement in learning Psycholinguistics or not. The subjects and objects of product trials on an expanded scale will be given to students of the English department study program FITK UIN North Sumatra Medan. The type of quantitative data, using a Likert scale questionnaire instrument was used to collect data. The validity test analysis technique uses the Aiken and Cronbach Alpha formulas for reliability. The research will produce articles published in reputable national or international journals and Intellectual Property Rights (HaKI), which are empirically proven to be valid, practical and effective.